2018
DOI: 10.21273/hortsci10746-18
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Root Architecture Attributes at the Onset of Storage Root Formation among Resistant and Susceptible Sweetpotato Cultivars Infected with Meloidogyne incognita

Abstract: In sweetpotato (Ipomoea batatas), the successful emergence and development of lateral roots (LRs), the main determinant of root system architecture (RSA), determines the competency of adventitious roots (ARs) to undergo storage root formation. The present study investigated the effect of three levels of root-knot nematode (RKN) inoculum of race 3 of Meloidogyne incognita on LR length, number, area, and volume in ‘Beauregard’, ‘Evangeline’, and ‘Bayo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
2
8
1
Order By: Relevance
“…This response corroborates prior findings that increased Pi availability is associated with storage length increases in BB and BX . The early onset of storage root formation in BB relative to other cultivars is consistent with past findings of storage root formation at 20 d in BX and EV in similar growing conditions (Villordon and Clark, 2018;Villordon et al, 2009a). Among the cultivars used in the current study, BB consistently produces relatively higher storage root yields in multiyear and multilocation field trials (Table 1) (LaBonte et al, 2013).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This response corroborates prior findings that increased Pi availability is associated with storage length increases in BB and BX . The early onset of storage root formation in BB relative to other cultivars is consistent with past findings of storage root formation at 20 d in BX and EV in similar growing conditions (Villordon and Clark, 2018;Villordon et al, 2009a). Among the cultivars used in the current study, BB consistently produces relatively higher storage root yields in multiyear and multilocation field trials (Table 1) (LaBonte et al, 2013).…”
Section: Resultssupporting
confidence: 89%
“…However, the direct relationship between LR development and anatomical cues associated with the onset of storage root formation has only recently been documented for the cultivar Beauregard (Villordon et al, 2012a). Linking root architecture attributes to storage root formation in sweetpotato paved the way for the systematic investigation of biotic and abiotic variables known to directly or indirectly influence sweetpotato storage root yield potential, including water availability (Villordon et al, 2012a), nitrogen variability (Villordon et al, 2013), virus presence (Villordon and Clark, 2014), and nematode infection (Villordon and Clark, 2018). Regarding sweetpotato in particular, there is increasing interest in understanding the biological and environmental variables that influence primary or main root length because this is directly related to the determination of storage root length and shape (Villordon et al, 2020).…”
mentioning
confidence: 99%
“…1B), supporting the hypothesis that the high B level used in this study did not suppress, but only delayed SR formation. The early onset of SR formation in BX relative to other cultivars is consistent with past findings in which SR formation was detected at 15 to 20 d in BX in similar growing conditions (Villordon and Clark, 2018;Villordon et al, 2009Villordon et al, , 2020. Among the cultivars used in the current study, BX consistently produces relatively higher SR yields in multiyear and multilocation field trials (Table 1; LaBonte et al, 2013).…”
Section: Resultssupporting
confidence: 90%
“…fimbriata affects RSA development can inform whether or not it is important to manage the pathogen during field production rather than the current approach of managing infections at harvest, and during SR planting and slip transplanting. Past work showed that biotic factors such as viruses (Villordon & Clark, 2014) and nematodes (Villordon & Clark, 2018) directly influence LR development and both have been associated with reduced SR yield and quality in sweet potato (Clark et al., 2013). Such findings provide evidence about the potential influence of biotic factors on RSA development in sweet potato.…”
Section: Introductionmentioning
confidence: 99%
“…fimbriata . Bayou Belle and Beauregard have been used as models for the study of factors affecting RSA (Villordon et al., 2012, 2018, 2020; Villordon & Clark, 2014, 2018).…”
Section: Introductionmentioning
confidence: 99%